"I Go Outdoors for Activities Every Day": Go-Along With Seniors With Slow Walking Speeds to Explore Environmental Factors Influencing Mobility - Yanchuan Mou; Yanchuan Mou; Yu Qin; Shaofei Niu (Frontiers Media S.A., 2024)
ObjectivesThis study aims to: 1) Explore the mobility experiences of seniors with slow walking speeds (SSWS) in urban neighborhoods; and 2) Investigate their environmental barriers and supports.MethodsGo-along interviews were conducted with 36 SSWS residing in urban neighborhoods of Chongqing City, China. The mobility patterns and built environment factors influencing their mobility were revealed through cartographic analysis and thematic analysis.ResultsSSWS primarily focused their activities within a 400-meter radius of their homes. Built environment themes included topography, neighborhood services, sidewalks, seating, traffic safety, weather, greenery, and lighting. Significant mobility barriers included long stairs, steep slopes, fast-moving objects on sidewalks, road crossings, and fast traffic. Available handrails, nearby food-service places, ample seating, and greenery were identified as supportive factors for their mobility.ConclusionThis study stands out as the first to specifically examine the mobility of SSWS within the built environment. We suggest that SSWS should be taken into account when establishing a benchmark for general design frameworks. These improvements not only contribute to the mobility of slow walkers but also have positive impacts on the broader population.